Is a 'Factory Southern Africa' Feasible? Harnessing Flying Geese to the South African Gateway - Peter Draper; Andreas Freytag; Sören Scholvin; Luong Thanh Tran (Center for Economic Studies and ifo Institute (CESifo), 2016)
The countries comprising the Southern African Customs Union (SACU) are currently not very integrated into global value chains (GVCs), potentially missing out on important development opportunities. Accordingly, we explore high level options for promoting their integration. Given East Asia's spectacular success with integrating into GVCs, we first assess the probability that SACU can copy their flying geese pattern. That was initiated by Japanese multinational corporations (MNCs) investing in successive EastAsian countries thereby becoming the lead geese, to be joined subsequently by MNCs from other countries. We argue that the conditions for pursuing a flying geese approach are difficult to replicate in SACU. Therefore, we proffer and explore the proposition that South Africa could serve as the gateway for harnessing MNC geese flying from third countries into the SACU region, in time propelling regional development through knowledge and investment spillovers, and serving as a conduit into GVCs. However, there may be substantial obstacles to deepening this integration potential. Other African gateways are emerging as alternatives to South Africa. And some SACU governments would prefer to build regional value chains (RVCs) rather than prioritise GVC integration. We argue that RVCs are complements to GVCs. SACU countries, excluding South Africa, may not attract many world leading MNCs since their markets are small, but could attract smaller regional players from South Africa or elsewhere. Thus building RVCs in the short run could assist with integration into GVCs in the longer run. Overall, this requires harnessing South African and MNC geese to the South African gateway, in a mutually complementary strategy.
Keywords: F15; F23; 330